2020
DOI: 10.3389/fgene.2020.00112
|View full text |Cite
|
Sign up to set email alerts
|

Human Hepatic Cancer Stem Cells (HCSCs) Markers Correlated With Immune Infiltrates Reveal Prognostic Significance of Hepatocellular Carcinoma

Abstract: Background: Several markers have been reported to be specific for hepatic cancer stem cells (HCSCs), which is usually thought to be highly associated with poor clinical outcomes. Tumor-infiltrating immune cells act as an important factor for oncogenesis. Little is known about the correlation of HCSC markers to prognosis and immune infiltrates.Methods: Expression of HCSC markers was analyzed through Oncomine database, Gene Expression Profiling Interactive Analysis (GEPIA) and Integrative Molecular Database of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Yet another A1CF target, Sox9 mRNA, which was immunoprecipitated from hepatocytes from A1cf +/Tg mice, was identified as a hepatic stem cell marker in HCC with SOX9 overexpression in patients correlating with reduced overall survival (47).…”
Section: Discussionmentioning
confidence: 99%
“…Yet another A1CF target, Sox9 mRNA, which was immunoprecipitated from hepatocytes from A1cf +/Tg mice, was identified as a hepatic stem cell marker in HCC with SOX9 overexpression in patients correlating with reduced overall survival (47).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironment (TME) contributes largely to the development of tumor heterogeneity and the development of tumors [ 18 ]. In the TME, immune infiltration patterns are valuable for prognostic assessment in HCC [ 19 ]. The interdependent relationship between tumor metabolism and immune infiltration has been reported in previous studies as well [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the expression of CSC makers in human tumor tissues is correlated with the number of tumor-infiltrating immune cells [ 34 , 35 ], suggesting that CSCs exhibit a close relationship with the tumor immune environment. Accumulating evidence suggests that the immune response to CSCs is frequently compromised because of their immune evasion properties.…”
Section: Immunosuppressive Properties Endowed On Cscsmentioning
confidence: 99%